(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Despite the tireless research of scientists around the world, we are witnessing the prevalence of coronavirus disease, and many questions about the etiology, course, prevention, and rehabilitation of the disease remain open. Experiments by health professionals have shown that coronavirus infection was mostly mild to moderate, but severe and lethal cases were observed in about 40 percent of patients. Of course, it was noted that the condition of the patient’s immune system, as well as the patient’s age, the presence of co-morbidities, and harmful habits are of great importance. Suppose a patient with COVID-19 infection is rehabilitated from the first days of his illness and its continuity is established. In that case, the rate of not only death but also admission to the intensive care unit of many patients will be sharply reduced [3].